THE INFLUENCE OF MOTIVATION ON EMPLOYEE PERFORMANCE THROUGH COMPENSATION AS MEDIATION - Supriatna, Dadang; Narimawati, Umi; Sunarsi, Denok (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2024)
This research investigates the relationship between employee motivation and performance at PT Karunia Gemilang, using an associative quantitative approach. The total sample used was 65 employees, representing all members of the company's population. Data analysis includes validity, reliability, simple linear regression, correlation coefficient analysis, and coefficient of determination. The results show that there is a strong and significant relationship between motivation and employee performance. The correlation coefficient of 0.768 indicates that motivation has a substantial influence on employee performance. Furthermore, the coefficient of determination of 59.0% indicates that most of the variability in employee performance can be explained by variability in their motivation. These findings emphasize the importance of effective motivation strategies in human resource management to optimize employee performance. This study highlights the important role of motivation in achieving organizational goals and increasing employee work effectiveness.